Klasifikasi Kebakaran Hutan Menggunakan Metode K-Nearest Neighbor : Studi Kasus Hutan Provinsi Kalimantan Barat - Ari Rudiyan; Akhmad Erik Dzulkifli; Khabib Munazar (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
A very wide forest could cause natural disaster such as forest fire that resulting losses to inhabitant, one of which effecting health and safety. West Kalimantan province is one of the province in Indonesia that has wide area of forest with 8,200,000 ha of forest and 1,600,000 ha of peatland all over the Kalimantan Island. Therefor this study is focusing on the data of west Kalimantan province forest. The aim of the study is to classify forest fire in West Kalimantan Province and followed by designing a REST API application of forest fire detector. In hope that in future, the application will be useful to prevent forest fire in the area of west Kalimantan Province. K-Nearest Neighbor method and balltree algorithm are used in this study to collect and process the data. The sample that are collected about 30% of 14,201 data with accuracy up to 92% with K = 18.